Comparison of immediate effect of instrument assisted soft tissue mobilization versus muscle energy technique along with hot pack on pain and range of motion in individuals with heel pain - Kubal, Swati V.; Lokwani, Mahek D. (International Journal of Research in Orthopaedics, 2026)
Background: Heel pain is a common musculoskeletal complaint that affects daily activities and mobility. Various therapeutic interventions, including instrument assisted soft tissue mobilization (IASTM) and muscle energy technique (MET), are employed to alleviate pain and improve range of motion (ROM). However, limited studies compare their immediate effectiveness. This study aimed to compare the immediate effects of IASTM versus MET along with hot pack on pain and ankle dorsiflexion ROM in individuals with unilateral heel pain. Methods: A total of 60 participants with unilateral heel pain were randomly allocated into two groups: Group A (IASTM) and Group B (MET with hot pack), with 30 participants in each. Pain was assessed using the visual analog scale (VAS) and ankle dorsiflexion ROM was measured using a clinometer smartphone application. Pre- and post-intervention assessments were conducted. A Wilcoxon signed-rank test and paired t-tests were used for within-group comparisons, while the Mann-Whitney U Test and unpaired t-test were used for between-group comparisons. Results: Both interventions significantly reduced pain and improved dorsiflexion ROM (p<0.001). However, the IASTM group exhibited a greater reduction in VAS scores (Z=-4.893, p<0.001) and significant increase in dorsiflexion ROM (t =-40.934, p<0.001) compared to the MET with hot pack group (Z=-4.977, p<0.001) (t=-15.642, p<0.001). Between-group analysis further confirmed that IASTM was superior to MET with a hot pack in both pain reduction (U=153, p<0.001) and ROM improvement (t=3.604, p=0.001). Conclusions: Both IASTM and MET with a hot pack are effective in reducing heel pain and improving dorsiflexion ROM.